2012
DOI: 10.5217/ir.2012.10.2.176
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for RecurrentClostridium difficileInfection

Abstract: Background/Aims: Clostridium difficile infection (CDI) is a common nosocomial infection associated with substantial morbidity, mortality and increased medical care costs. Although most patients initially respond to therapy, with either metronidazole or vancomycin, about 15-20% of patients experience recurrence. The aim of this study was to analyze the risk factors related to recurrent CDI (RCDI). Methods: We retrospectively reviewed data, from patients diagnosed with CDI during admission at a university hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…In addition, other known CDI recurrence trigger conditions include: (1) patients older than 65 years of age, (2) continuous antibiotic usage, (3) failure to provide proper treatment, and (4) suppressed patient immune systems 32,33,34,35. However, re-infection with new strains is believed to be mainly responsible for CDI recurrence (48-75%) 14,34,35,36. In this respect, it is meaningful that nasogastric tube insertion increases the risk of CDI up to 9-fold as manipulation of contaminated instruments can transfer C. difficile strains from hospital environments 37.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, other known CDI recurrence trigger conditions include: (1) patients older than 65 years of age, (2) continuous antibiotic usage, (3) failure to provide proper treatment, and (4) suppressed patient immune systems 32,33,34,35. However, re-infection with new strains is believed to be mainly responsible for CDI recurrence (48-75%) 14,34,35,36. In this respect, it is meaningful that nasogastric tube insertion increases the risk of CDI up to 9-fold as manipulation of contaminated instruments can transfer C. difficile strains from hospital environments 37.…”
Section: Discussionmentioning
confidence: 99%
“…Basically, unnecessary use of broad-spectrum antibiotics should be avoided and more emphasis should be placed on hygiene management such as washing hands. In addition, more active preventive measurements should be discussed; for instance, an aseptic method for nasogastric tube insertion might be worthwhile to consider for patients with a history of CDI 14. Lastly, additional investigations are needed to distinguish if recurrence was caused by the same strain or re-infection by other strains by analyzing samples from patients with chronic recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for recurrent CDI included antibiotic therapy, anaemia, and tube feeding in one study [23], while another found proton pump inhibitor (PPI) use alone was associated with recurrent disease [24]. One study found that the proportion of community-acquired CDI (CA-CDI) among all CDI cases within a Busan hospital was 7.1% [25], while another reported that 59.4% of cases of CDI presenting at the emergency department of a Seoul hospital were community-acquired [26].…”
Section: Introductionmentioning
confidence: 99%
“…These suggested that the epidemiology of C. difficile was not only caused by one or a few hypervirulent ribotypes but also included a diversity of strains in causing the infection. In Asia, hypervirulent ribotype 027 strain only occurred sporadically, with the most prevalent ribotypes being 002, 017, 018, 014 and 012 [19,[35][36][37][38][39][40][41]. In Hong Kong, the rising incidence and disease burden of CDI have been reported, with the most common ribotypes being 002 (22.8%), 012 (14.1%), 014 (14.1%) and 046 (13.0%) [42].…”
Section: Introductionmentioning
confidence: 99%